Kualitas Produk dan Harga Berpengaruh Terhadap Loyalitas Melalui Kepercayaan Pelanggan di Rumah Makan 2 Tak Ampera Cabang Veteran, Jakarta Selatan - Adawiyah, Robiatul; Amrullah, Amrullah; Wicaksono, Haryo; Chairani, Alda; Sakti, Pricilia Johani (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2025)
This study aims to analyze the effect of product quality and price on customer loyalty at Rumah Makan Ampera 2 Tak, Veteran Branch, Bandung, with trust as a mediating variable. A quantitative approach was used, employing Structural Equation Modeling (SEM) with Partial Least Squares (SmartPLS 4.0). Data were collected from 150 respondents through a questionnaire distributed to customers who had visited the restaurant more than twice. The results show that both product quality and price significantly influence customer trust and loyalty. Moreover, trust is proven to mediate the relationship between product quality and price on customer loyalty. These findings indicate that consistent food quality, high-quality ingredients, hygienic presentation, and fair, transparent pricing are crucial factors in building trust and maintaining customer loyalty. In conclusion, trust serves as a key element that bridges customers' perceptions of product and price with their decision to remain loyal. It is recommended that the management maintain food quality standards and pricing transparency, while also enhancing communication and service to build sustainable customer trust. Keywords: product quality, price, trust, customer loyalty